Respuesta :
The solution of any two system of equations is the point of intersection of the two lines represented by the equations.
Hence, the solution to the system of equations: y = −2x + 3 and y = −x + 6 is line y = −2x + 3 intersects the line y = −x + 6.
Hence, the solution to the system of equations: y = −2x + 3 and y = −x + 6 is line y = −2x + 3 intersects the line y = −x + 6.
Answer:
C. Line [tex]y = -2x + 3[/tex] intersect the line [tex]y = -x + 6[/tex].
Step-by-step explanation:
We are given that,
The system of equations is [tex]y = -2x + 3[/tex] and [tex]y = -x + 6[/tex].
Subtracting the equations gives us -x=3 i.e. x= -3.
Substituting the value of x in any equation, we get,
[tex]y = -x + 6[/tex] implies [tex]y = -(-3)+ 6[/tex] i.e. y = 3+6 i.e. y= 9.
Thus the solution of the equations is x= -3 and y= 9.
Plotting the equations, we see that,
The graphs of the equations intersect at the point (-3,9).
Hence, both lines intersect each other.
![Ver imagen wagonbelleville](https://us-static.z-dn.net/files/d75/63876c49a826653658e5853d05f3577f.jpg)